Gender differences in lung cancer epidemiology – do Austrian male lung cancer patients still die earlier in life? - Felsinger, Richard; Kunze, Ursula; Groman, Ernest (Frontiers in Public Health, 2023)
Objective: Previous analyses reported an unexpected decline of mean age of death of Austrian male lung cancer patients until 1996 and a subsequent turnaround of this epidemiological trend after the mid-1990s until 2007. In light of ongoing changes in smoking behavior of men and women, this study aims to investigate the development of mean age of death from lung cancer in Austria during the past three decades. Material and methods: This study used data about the annual mean age of death from lung cancer, including malignant neoplasm of trachea, bronchus and lung, between 1992 and 2021 obtained from Statistics Austria, Federal Institution under Public Law. One-way analysis of variance (ANOVA) and independent samples t-tests were applied to explore any significant differences of mean values in the course of time as well as between men and women. Results: Overall, mean age of death of male lung cancer patients increased consistently throughout the observed time periods, whereas women did not show any statistically significant change in the last decades. Conclusion: Possible reasons for the reported epidemiological development are discussed in this article. Research and Public Health measures should increasingly focus on smoking behaviors of female adolescents.